Modelling of spruce forest decay caused by the European spruce bark beetle in the area of Bohemian Forest using GIS - Brož, Zdeněk (Jihočeská univerzita, 2016)
This thesis deals with the bark beetle population gradation which resulted in dieback of montane spruce forest in the central part of the Bohemian Forest, Czech Republic, during 1991 - 2000. A spatio-temporal model of changing land cover has been made using remote sensing and GIS methods. The statistical analyses have been made using generalized linear models (GLM). The possible effect of various conditions and environmental factors at landscape as well as the stand level has been discussed.
Modelling of spruce forest decay caused by the European spruce bark beetle in the area of Bohemian Forest using GIS
Keywords: lýkožrout smrkový; Ips typographus; národní park Šumava; populační gradace; časoprostorový model; dálkový průzkum země; GIS; GLM; European spruce bark beetle; Ips typographus; Šumava National Park; population outbreak; spatio-temporal model; remote sensing; GIS; GLM